1997
DOI: 10.1093/molehr/3.6.467
|View full text |Cite
|
Sign up to set email alerts
|

The expression of leptin and its receptors in pre-ovulatory human follicles

Abstract: The expression of leptin and its receptors was examined by reverse transcriptase-polymerase chain reaction and immunofluorescence in granulosa and cumulus cells of pre-ovulatory follicles and in meiotically mature oocytes obtained from women undergoing in-vitro fertilization. Leptin concentrations were measured in newly aspirated follicular fluids and in maternal serum before and after the administration of an ovulatory dose of human chorionic gonadotrophin. The findings demonstrate leptin expression at the mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
173
6
22

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(215 citation statements)
references
References 18 publications
12
173
6
22
Order By: Relevance
“…We showed that, secondary to a leptin increase, the serum L:A ratio increased with exogenous gonadotropins. Given that serum and follicular levels of leptin were tightly correlated and essentially equivalent, we concluded that intrafollicular levels were derived mostly from serum transudation, and very little if at all from ovarian production, despite the known expression of leptin and its receptor in human preovulatory follicles [7]. In the linear regression model, FF insulin predicted FF leptin and the L:A ratio independently, while it indirectly correlated with FF adiponectin via leptin.…”
Section: Discussionmentioning
confidence: 82%
“…We showed that, secondary to a leptin increase, the serum L:A ratio increased with exogenous gonadotropins. Given that serum and follicular levels of leptin were tightly correlated and essentially equivalent, we concluded that intrafollicular levels were derived mostly from serum transudation, and very little if at all from ovarian production, despite the known expression of leptin and its receptor in human preovulatory follicles [7]. In the linear regression model, FF insulin predicted FF leptin and the L:A ratio independently, while it indirectly correlated with FF adiponectin via leptin.…”
Section: Discussionmentioning
confidence: 82%
“…Leptin protein has been found in follicular fluid, with concentrations corresponding to those reported in serum [55]. Leptin plays a role in both follicular development, where leptin transcript has been detected at early follicular stages, whereas leptin protein appears only in mature follicles [56], and subsequent luteal function.…”
Section: Role Of Leptin In Ovary Functionmentioning
confidence: 75%
“…Leptin is a secreted protein produced in adipocytes; its secretion increases with food intake and decreases during starvation. Its primary site of action is the hypothalamus; however, the leptin receptor has also been indentified in rodent and human theca cells, granulosa cells, oocytes, and embryos [51,52]. In rodent models, high concentrations of leptin can impair follicle development, ovulation, and oocyte maturation [53,54].…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 99%